Seasonal variations of cauda epididymal spermatozoa of bucks (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The study was conducted to evaluate the influence of season on cauda epididymal spermatozoa isolated from bucks.Materials and methods: Testes of 30 mature bucks were collected from local slaughter house, and were processed for the retrieval of cauda epididymal spermatozoa for evaluation. Testes were collected in three seasons (winter, summer and rainy), and each season was having 10 pairs of testicles. Recovered spermatozoa from the cauda epididymis were processed immediately for evaluation of semen attributes (Spermatozoa motility, viability, plasma membrane integrity, acrosomal status and DNA integrity).Results: Physiological effect of season was observed on progressive motility, percent of live spermatozoa, spermatozoal membrane integrity (HOST), acrosomal integrity, capacitation status and DNA integrity. Progressive motility, percent live spermatozoa, HOST positive spermatozoa, were found significantly (P